Effektivitas Disaster Training terhadap Peningkatan Pengetahuan, Sikap dan Keterampilan Perawat dalam Kesiapsiagaan Penanggulangan Bencana Letusan Gunung Kelud di Kota Blitar - Agus Khoirul Anam; Sri Winarni; Budi Susatya (STIKes Patria Husada Blitar, 2015)
Disaster preparedness is a series of efforts made to anticipate the disaster through organizing as well as the steps effectively and usefull. Identification of factors influencing nursing preparedness is beneficial in the preparation of government programs related to nursing preparedness in disaster management and nurses understand the factors that need to be considered.This study aimed to identify the efectiveness of disaster training to enhance knowledge, attitude and skill nurses in disaster management.Methode :This research is pre experimental pretest posttest design . The number of samples is s 30 nurses who were in the Disaster-prone Region Kelud in Blitar district and the study was conducted on Oktober 16. Result of analysis used wilcoxon significancy 0,000 ( p< 0,05 ) that shows the dfference influencing knowledge, attitude and skill nurses after Disaster Training . Discussion: Disaster Training is very important to improve nursing preparedness in facing disaster. Nurse assocation and goverment must be able to give good support for disaster nurse.